Little Bird finds her voice - Swift, Christine; Endersby, Frank (London : Alligator Products, Ltd., 2023)
"Little Bird is shy, she can't sing like the other birds. One day she has to be very, very brave and discovers she too can sing beautiful songs."
Primary
Keywords: Birds -- Fiction